The Deliberative Approach In Teaching Dialogue Texts To Middle School Students/ Ø§Ù„Ù…Ù‚Ø§Ø±Ø¨Ø© Ø§Ù„ØªØ¯Ø§ÙˆÙ„ÙŠØ© ÙÙŠ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„ØÙˆØ§Ø±ÙŠØ© Ù„ØªÙ„Ø§Ù…ÙŠØ° Ø§Ù„Ù…Ø±ØÙ„Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© - Hafida, Bourouba; Khelifa, Sahraoui; Mokrane, Fecih (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This research deals with the deliberative approach in teaching the dialogic text in middle school;given the importance of this approach, which is concerned with language during its use and goes beyond the vocalized formto search for its hidden meaning and purposes. This research was initiated by defining the terms of the study;then we dealt with the reality of teaching the dialogue text in the middle stage, where we reviewed the method or approach by which the dialogue text is taught in the Algerian middle school.The research also included the importance of adopting the deliberative approach in teaching the dialogue text and the method of investing it in the learning-teaching process.As the most appropriate alternative, given the mechanisms and techniques it provides that make the process of teaching the dialogue text more interactive and active, then we concluded the research with a set of results that we reached. The main approach that we adopted in this research is the qualitative approach which is based on collecting qualitative data as a first stage, and then we used qualitative analysis in presenting and analyzing this data and through discussing of these data, we came to important results and conclusions. As for the type; we have relied this study through our attempt to search for methods and techniques dialogue texts to middle school students and their suitability to the nature of the dialogue text. As it a communicative text, in its teaching we need an approach that touches its various interactive aspects; Whether it is apparent or implicit on the one hand, and also the effectiveness of these methods in stimulating motivation, suspense and attracted students on the other hand; We also relied on primary and secondary sources. And we have reached a set of conclusions, which summarize it stressing the importance of adopting the deliberative approach in teaching dialogic texts. This is due to the mechanisms and techniques that provides it and make the process of teaching the dialogue text more interactive and dynamic